PEMANFAATAN RUMPUT LAUT Sargassum sp. SEBAGAI ADSORBEN LIMBAH CAIR INDUSTRI RUMAH TANGGA PERIKANAN - Ibrahim, Bustami; Sukarsa, Dadi Rochnadi; Aryanti, Linda (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Seaweed Sargassum sp. is able to adsorb organic materials in fisheries liquid waste because it contain polysaccharides, protein and lipid in cell wall surface that consist of functional groups like amino, hydroxil, carboxyl and sulfate. This research aims were to determined the utilization of Sargassum as an adsorbent, the effect of chemical modification of Sargassum and adsorbent’s weight in ability to adsorb fisheries liquid waste. Some parameters were tested in this research. Colour of liquid waste was observed visually, pH of liquid waste was tested by pH meter, turbidity was tested by turbidimeter, total suspended solids (TSS) was tested by gravimetry method and chemical oxygen demand (COD) was tested by closed reflux with titrimetry method. Reduction COD value of fisheries home industry liquid waste optimally can be achieved by Sargassum modified by acid. Optimal performance was obtained when the weight value of adsorbent between  1.0-2.0 gram in 100 ml liquid waste. Generally, optimal weight of adsorbent in order to reduce organic compounds was 1.0 gram in 100 mL fisheries home industry liquid waste. Using 1.0 gram Sargassum with acid modification made the liquid waste colour almost clearly, reached a pH level of 4.84, decreased turbidity level of 245 NTU, decreased TSS level of 851.7 mg/L and COD level of 720 mg/L.Keyword: acid modification, adsorb, adsorbent, fisheries liquid waste, Sargassum sp.